ARTIFICIAL INTELLIGENCE IN THE SPHERE OF UNIVERSITY EDUCATION - Yordanova, Steliana (E-Journal VFU, 2024)
A fragmentary analysis of classical and smart (intelligent) universities has been made, as well as the change in attitudes, approaches and methods of application of a modern educational paradigm as a result of the application of artificial intelligence in current university practice. The role of classical universities is emphasized not only as a powerful tool for storing and transmitting knowledge, but also for educating young people. We believe that the development of higher education has a huge impact on the total invasion of smart technologies into current social practice. Questions related to the synthesis, accumulation and preservation of knowledge and skills through the educational paradigm "learning by doing" (John Dewey ) in the university educational environment is placed in the focus of the global and sustainable development of society. The impact of the mass distribution of artificial intelligence in various social groups, through the implementation of innovative and practice-related university education, is examined. Axiomatic changes in attitudes towards conducting R&D are defined, and the moral constraints faced by scientists and university professors are discussed when doing their research related to the development and implementation of artificial intelligence systems, both virtual and in real work environment.
Keywords: Artificial intelligence; learning by doing; educational paradigm; universities; information; knowledge; R&D